Influence of genotypes and crop growth stage at time of infection on seed transmission of Maize chlorotic mottle virus - Kimani, Esther; Cyrus Mugambi Micheni; Laureen Gatwiri Muriki; Samuel Mwaura Kiarie; Miano, Douglas Watuku; Macharia, Isaac; Muiru, William Maina; Prasanna, Boddupalli M.; Wangai, Anne (Informa UK Limited, 2024)
Understanding the effect of seed transmission of Maize chlorotic mottle virus (MCMV) is important in managing the spread of the disease especially secondary transmission caused by vectors. This study was set out to investigate the effect of different genotypes and crop growth stage at the time of infection to rate of MCMV transmission from seeds to seedlings. The experiments were laid out in randomised complete block design with three replications. Detection of MCMV in the grow outs was determined using double antibody sandwich enzyme-linked immunosorbent assay and real time reverse transcription polymerase chain reaction. The results showed low rates of seed transmission from the genotypes in which their was detection of MCMV in their samples (0.08-1%). Similarly, crop growth stage at time of infection also showed low transmission rate of up to 0.1%, with highest transmission rate at the four-leaf stage.